EQ Spacing Quality Control Using Statistical Quality Control and Fault Tree Analysis at PT Sinar Semesta - Ahmad Zada Hilmi Syifa’; Ayudyah Eka Apsari (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
PT Sinar Semesta is a company engaged in the metal casting industry. In its production process, defects were still found during the period from March 2023 to February 2024. Out of a total production of 4,950 units, there were 1,004 defective units, consisting of 534 units with flow error defects and 470 units with porosity defects. To address this issue, quality control methods such as Statistical Quality Control (SQC) and Fault Tree Analysis (FTA) are necessary to minimize product defects, improve quality, and maintain high standards. Based on the Pareto diagram, the most dominant defect percentages are flow error defects at 53.19% and porosity defects at 46.81%. The control chart shows points beyond the upper control limit (UCL) occurring in April with 148 units, May with 145 units, and October with 149 units, and below the lower control limit (LCL) occurring in August with 35 units, January with 36 units, and February with 32 units. Based on the fault tree analysis, five main factors causing defects were identified: human, machine, raw material, method, and environment. Proposed improvements include operator training, routine machine maintenance, accurate raw material measurement, use of high-quality raw materials, pre-pouring temperature checks, increased supervision, and environmental improvements.